Development of biodegradable protein-based films incorporated with mango kernal extract for active packaging of mayonnaise - Zainal Arifin, Maryam 'Adilah (2018)
Active packaging is a novel idea in which active substance such as antioxidant is incorporated into the packaging to prolong the shelf-life and maintain the quality of food product. This research was focused on developing active packaging by using food industries’ by-products. In the first objective, soy protein isolate (SPI) and fish gelatin (FG) were used as the source of biopolymers and different concentration (1, 3 and 5%) of mango kernel extracts (MKE) were added as natural antioxidants. The addition of MKE produced thicker and more opaque films (p < 0.05), increased the tensile strength (p < 0.05) and antioxidant activity (p < 0.05) but decreased the water solubility (p < 0.05). The overall observations revealed that SPI outperformed FG as active packaging films. In the second objective, the storage stability of antioxidant films was studied at 25°C, 4°C and -18°C for 90 days. The temperature and time did not have significant effect (p > 0.05) on thickness and colour. All the films showed an increase in tensile strength, decrease in elongation and increase in Young’s modulus (p < 0.05). The highest decrease in antioxidant activity was only 4% throughout the storage time. This shows that the antioxidant activity of the films is stable for the 90 days of storage. In the third objective, the mayonnaise packaged in control and SPI+MKE films turn significantly (p < 0.05) darker and the pH values significantly (p < 0.05) increased after 6 weeks of storage. The SPI+MKE films were able to slow down the lipid oxidation by 30% in peroxide value analysis, 44% in TBARS analysis, 38% in anisidine value analysis and 65% in total oxidation analysis. Therefore, the usage of the SPI+MKE films could maintain the quality of mayonnaise for a longer time.